The Bioinformatics Analysis of Aldosterone-Producing Adenoma and Verification of Differentially Expressed Genes - Yinjie Gao; Xiaosen Ma; Huiping Wang; Yunying Cui; Yushi Zhang; Min Nie; Anli Tong (International Journal of Endocrinology)
Purpose. Previous studies have investigated the transcriptional modulations of aldosterone overproduction of aldosterone-producing adenomas (APAs). We aimed to systematically study the genes and pathways associated with molecular mechanism underlying APA by bioinformatics analysis and experimental validation for the expression profile. Methods. This study was performed based on three gene expression profiles (GSE64957, GSE8514, and GSE60042). Differentially expressed gene (DEG) investigation, function and pathway enrichment analysis, and protein-protein interaction (PPI) network analysis were performed by the bioinformatics analysis. For the validation with quantitative PCR, tissues from 11 patients with nonfunctioning adrenal adenoma (NFA) and 13 with APA were included in our cohort. Results. In this study, the bioinformatics analysis was performed and 182 upregulated and 88 downregulated DEGs were identified. As expected, the upregulated DEGs were primarily involved in calcium ion homeostasis (p = 2.00X10−4). In the KEGG pathway analysis, calcium signaling pathway (p = 4.38X10−6) and the aldosterone synthesis and secretion (p = 8.73X10−6) were enriched. Moreover, quantitative PCR was performed to detect the expression of 7 upregulated genes (PCP4, ATP2A3, CYP11B2, CLCN5, HTR4, VDR, and AQP2) among the intersection of DEGs. The mRNA levels of CYP11B2, HTR4, and AQP2 were significantly increased in APA samples compared to NFA (24.420 folds of NFA, p < 0.001; 3.753 folds of NFA, p = 0.002; and 11.487 folds of NFA, p = 0.018). Conclusion. In summary, the present study showed several candidate genes with high expression from bioinformatics analysis and our cohort. Also, the DEGs were enriched in aldosterone synthesis and secretion and calcium signaling pathway as expected.